KONDISI PADANG LAMUN DI SEKITAR PERAIRAN DESA BOWONGKALI KECAMATAN TABUKAN TENGAH KABUPATEN KEPULAUAN SANGIHE - Dedyes Alescandro Darui; Calvyn F. A. Sondak; Veibe Warouw; Kurniati Kemer; Grevo Soleman Gerung; Billy Theodorus Wagey (Sam Ratulangi University, 2024)
Seagrass is a flowering plant (Angiospermae) that can live in the sea. Seagrass ecosystems have a very important role both ecologically and biologically in coastal and estuary areas. These plants provide food for many marine animals include herbivorous invertebrates, and herbivorous fish. This study aims to determine the condition of seagrass beds in the waters of Bowongkali Village, Central Tabukan District, Sangihe Islands Regency based on the percentage cover. Data collection method in this study uses the quadratic transect method with three transect lines with a length of 100m each and a distance between each transect is 50m. Data was collected by determining the percentage of seagrass cover and seagrass species composition in each small box in the quadrat frame on each transect. The results of this study obtained the total average percentage has a percentage value of seagrass cover of 48.67% and categorized as